Penerapan Arsitektur Metafora pada Perancangan Youth Center di Kota Padang - Nadya Yuliastri; Wahyuni Zahrah (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Youth center is a youth activity center in the form of a container or Aplace where teenagers can gather, socialize, and engage in arts, sports, education, and recreational activities. The lack of such facilities results in the low development of adolescents in the aspects of sports and arts. This can be the cause of juvenile delinquency due to the lack of control over youth leisure activities. Designing a youth center is needed to reduce the problem of juvenile delinquency, as well as to help develop the potential of teenagers in Padang city. This research aims to explore the design aspects and themes of the youth center building. This research uses a qualitative method by conducting a literature review and observation. The literature review was conducted to find out the types and typologies of youth center buildings as well as considerations related to youth center design requirements and standards. This design applies the architectural theme of wave metaphor to space, form, facade, color, and material, which illustrates the complexity of emotions and the journey of adolescent growth through the use of curved elements with various height variations.